2014
DOI: 10.1177/1091581814547422
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Deficiency of Werner Syndrome Protein or RECQ1 Promotes Genotoxic Potential of Hydroquinone and Benzo[a]pyrene Exposure

Abstract: The five known RecQ helicases in humans (RECQ1, BLM, WRN, RECQL4, and RECQ5) have demonstrated roles in diverse genome maintenance mechanisms but their functions in safeguarding the genome from environmental toxicants are poorly understood. Here, we have evaluated a potential role of WRN (mutated in Werner Syndrome) and RECQ1 (the most abundant homolog of WRN) in hydroquinone and benzo[a]pyrene-induced genotoxicity. Silencing of WRN or RECQ1 expression in HeLa cells increased their sensitivity to hydroquinone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(112 reference statements)
1
2
0
Order By: Relevance
“…As compared to control untreated U2OS cells, RECQ1 mRNA was also upregulated following treatment with chemotherapeutics 5-fluoro uracil (5-FU), gemcitabine, camptothecin as well as the laboratory carcinogen methylnitronitrosoguanidine (MNNG) and environmental mutagen benzo[a]pyrene ( Supplementary Figure 4 ). This is consistent with previous studies where RECQ1-depletion increased cellular sensitivity to camptothecin and benzo[a]pyrene [ 22 , 49 ].…”
Section: Resultssupporting
confidence: 93%
“…As compared to control untreated U2OS cells, RECQ1 mRNA was also upregulated following treatment with chemotherapeutics 5-fluoro uracil (5-FU), gemcitabine, camptothecin as well as the laboratory carcinogen methylnitronitrosoguanidine (MNNG) and environmental mutagen benzo[a]pyrene ( Supplementary Figure 4 ). This is consistent with previous studies where RECQ1-depletion increased cellular sensitivity to camptothecin and benzo[a]pyrene [ 22 , 49 ].…”
Section: Resultssupporting
confidence: 93%
“…For example, haplotypic analyses on different WRN coding SNPs indicated that Chinese workers exposed to benzene were more at risk of developing hematotoxicity depending on their polymorphic amino acids at both positions 1074 and 1367 [ 31 , 32 ]. Indeed, it has been reported that WRN plays an important role in the protection of cells against the toxicity of benzene metabolites [ 47 49 ]. Thus, the difference between the polymorphic WRN variants in the population is likely due to how each variant interacts with their nuclear partners in cells and how efficient the different enzymatic activities of the WRN containing complexes are performing in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Using the mouse model system, provided an indirect evidence for the DNA repair role for RecQL1 in the suppression of chromosome instability. Human cervical cancer cells deficient either in WRN or in RecQL1 were shown to be hypersensitive to hydroquinone and benzo(a) pyrene exposure indicating the participation of both WRN and RecQL1 proteins in the DSB repair pathway [Garige and Sharma, 2014]. Similar to RecQL1, RecQL5 also participates in DNA DSB repair [Schwendener et al, 2010;Maruyama et al, 2012;Paliwal et al, 2014], and the recruitment of RecQL5 to the sites of DNA DSBs depends on its interaction with a primary DSB sensor complex of 3 proteins: MRE11, RAD50, and NBS1 [Zheng et al, 2009].…”
Section: Recql4 Protects Cancer Cells From Endogenous and Exogenous Dna Damagementioning
confidence: 99%